2016
DOI: 10.1245/s10434-016-5583-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of the 12-Gene DCIS Score Assay: Impact on Radiotherapy Recommendations for Patients with Ductal Carcinoma In Situ

Abstract: ObjectiveThe aim of this study was to determine the impact of the results of the 12-gene DCIS Score assay on (i) radiotherapy recommendations for patients with pure ductal carcinoma in situ (DCIS) following breast-conserving surgery (BCS), and (ii) patient decisional conflict and state anxiety.MethodsThirteen sites across the US enrolled patients (March 2014–August 2015) with pure DCIS undergoing BCS. Prospectively collected data included clinicopathologic factors, physician estimates of local recurrence risk,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Such a low-cost approach would be beneficial, especially given that economic modeling found no circumstances in which the OncotypeDX assay could be cost-effective in determining who should receive RT ( 145 ). However, incorporating existing risk parameters in concert with a molecular assay could improve the predictive benefit, and a small clinical utility assessment found that patient anxiety and decisional conflict were reduced after receiving assay results ( 146 ).…”
Section: Biomarkers Of Recurrence and Progressionmentioning
confidence: 99%
“…Such a low-cost approach would be beneficial, especially given that economic modeling found no circumstances in which the OncotypeDX assay could be cost-effective in determining who should receive RT ( 145 ). However, incorporating existing risk parameters in concert with a molecular assay could improve the predictive benefit, and a small clinical utility assessment found that patient anxiety and decisional conflict were reduced after receiving assay results ( 146 ).…”
Section: Biomarkers Of Recurrence and Progressionmentioning
confidence: 99%
“…With these limitations acknowledged, our group participated in a multicenter study that found that the test may have certain clinical utility 45 . For example, in a patient who meets RTOG 9804 criteria for low risk DCIS (size ≤ 2.5 cm, mammographically detected, and low to intermediate grade), the estimated risk of IBTR is 1%/year treated without radiotherapy based on this trial data.…”
Section: Radiation Therapy For Dcismentioning
confidence: 99%
“… 24 , 25 Studies have found that use of the DCIS score can alter adjuvant therapy recommendations in up to 30% of patients, demonstrating the utility of genomic testing in providing additional information beyond clinical and pathologic factors alone. 26 Current assays have not yet been examined in the setting of IORT, and the validity and utility of doing so remains unclear. The results of our experience, however, highlight the need to further optimize patient selection for IORT.…”
Section: Discussionmentioning
confidence: 99%